Advanced Dosage Form Design: Role of Modified Natural Gums: A Review - Devi, Gayatri; Kaur, Malkiet; Nagpal, Manju; Sharma, Ameya; Puri, Vivek; Arora Dhingra, Gitika; Arora, Minaxi (Asian Journal of Chemistry, 2020)
Gums are naturally occurring segments in plants, which are cheap and abundant. Natural gums and their derivatives are widely used in a pharmaceutical dosage form. These natural materials possess several advantages over synthetic ones being chemically inert, non-toxic, low cost and biodegradable. However, quick degradation in the body, poor mechanical properties and low solubility are few disadvantages. To overcome these disadvantages, natural gums are modified by applying different chemical modification procedures. The modification of gums is done via various methods such as changing functional groups of gum, cross-linking with ions, grafting with polymers, sulfation, phosphorylation and thiolation. Modification of gums results in some superior properties which can be used in drug delivery applications. For example, change in crystallinity, improved solubility, stability, and improved mechanical properties are of use in development of modified drug delivery systems. Modified gums help to achieve pH dependent delivery and sustained delivery along with improved release kinetics of the drug. Current review covers various types of modifications in general and research literature on various medications of different gums (locust bean gum, cashew gum, moringa gum, xanthan gum, etc.). The modified natural gums and their derivatives can be the prospective carriers in the controlled drug delivery of drugs.